Analisis Tingkat Kepuasan Konsumen Terhadap Harga ( Price ) Susin di Kabupaten Sinjai (Studi Kasus di Desa Gunung Perak) - Wahyudir Kadir (State Islamic University (UIN) Alauddin, 2013)
ABSTRACT. This research was a case study that aims to determine: 1) the level of customer satisfaction of Sinjai’s dairy products (Susin), 2) Attributes (element) Sinjai’s milk (susin) was preferred by consumers. The experiment was conducted in the Perak Mountain village, West Sinjai, Sinjai Regency. The research method is a field survey by questionnaire survey instrumentation. Numbers of samples were determined by Skinov formula. Sampling purposive by 80 respondents had used. The results showed that: 1) The level of customer satisfaction with the product and price (2P) in the Perak Mount village Sinjai, consumers expressed satisfaction on all attributes of the products and prices of susin, 2) Consumer susin at Perak Mountain Village Sinjai priority susin flavor attributes of the product with the highest quantitative by 4.5811. Keywords: Satisfaction, Customer, Product and Price of Sinjai’s Milk (Susin).